(untitled) (Research, Society and Development, 2021)
The study aims at the circumstantial dynamics surrounding the environmental licensing of small hydroelectric plants (PCHs) in the state of Mato Grosso. It is characterized as qualitative, based on the intention to install SHPs in the Cuiabá River - MT, with information from studies of several articles, dissertations, theses and consultations carried out in the collection of the National Electric Energy Agency, of the National Water and Sanitation Agency and local media. It appears, in short, that the problem is not about the licensing capacity, but about the conflicts and possible impacts that may be generated from the implementation of SHPs, in general biodiversity, in the riverside communities that live in its around and downstream of the river, and mainly in fish reproduction. The study demonstrates a distinct occurrence of the community in relation to the implementation of SHPs in the Cuiabá river stretch, as compared to other implementation projects in the State, it gained particular attention from different members of society, such as prosecutors, judges, deputies, as well as from the academic sector, not only from the riverside community, demonstrating that the implementation of SHPs on the Cuiabá River, in addition to the commonly known impacts, demonstrates that the river’s importance goes beyond environmental aspects, promoting commotion among the region’s residents.